STUDENTS’ PERSPECTIVE ON FOREIGN TEACHER’S ONLINE TEACHING SKILLS IN INTERCULTURAL COMMUNICATION CLASS - Yoga Prihatin (University of Kuningan, 2022)
Internationalization in Post Covid-19 era changes the form of visiting scholar in Universitas Pancasakti Tegal. English Education of Universitas Pancasakti Tegal invites a Morrocan scholar to teach intercultural communication. The reason of inviting Moroccon scholar is first it is the implementation of MoU (Memorandum of Understanding) between Universitas Pancasakti Tegal and Hasan First University Morocco. The second reason is Intercultural communication crucial to bridge the communication among different countries with different cultural background. It is involving the diversity of at least two different cultures. It has created adjustment toward new learning environment for the students. The study investigates students’ perceptions on their first Moroccon teacher. The study used 45 second semester students of English Education who experienced the first foreign teacher in their study. The findings showed positive perceptions of students on their Moroccan teacher’s competencies in online teaching and the learning environment. The teacher has a good capability in technological skills, social and communication skills, design skills, content knowledge skills, pedagogical skills, and management and institutional skills. However, the problem of slow Internet connectivity and lack of Internet access for some of the students outside the university campus hindered the effectiveness of the online learning environment for a few students. Improvement in ICT infrastructure and capacity building for lecturers to adopt online learning approach were recommended.Keywords: online teaching competences; intercultural communication; students’ perceptions